Also called Marianet. Speaking in the Pleno Economico Ampliado. Text by the Secretary of Propaganda, dated 1939, June 18, of the Solidaridad Internacional Antifascista (SIA) on the back
Also called Marianet. Speaking in the Pleno Economico Ampliado. Text by the Secretary of Propaganda, dated 1939, June 18, of the Solidaridad Internacional Antifascista (SIA) on the back.